The correlation between certain facial and dental measurements that influence dental aesthetics "Cephalometric study" - Nadia H Hasan (University of Mosul, College of Dentistry, 2005)
The purpose of the present study was to assess and determine if the correlation between certain facial measurements was significant to recommend their use as reliable aesthetic factors for selection of suitable tooth moulds for anterior teeth restoration. The materials for this study included 50 cephalometric radiographs for selected undergraduate students of Dentistry Collage, Mosul University; 25 males and 25 females. The age ranged from 18-25 years old with normal occlusion. The data were analyzed by using Minitab system and the result confirmed that certain facial measurements considered directly to determine the outline form to restore anterior teeth such as tooth width at the incisor edge, incisor tooth length, intercanine distance, the ratio of incisor tooth length and tooth width at the incisor edge, bi-incisors width, and bi-orbital width, while the others, bi-zygomatic width, intermolar distance, anterior facial height, and the ratio of anterior facial height and bi-zygomatic width, were indirectly indicated. Also there was a significant difference between male and female groups with different facial measurements. The ratio of the anterior facial height to bi-zygomatic width for the total sample was 0.93 mm, while that for the tooth length to tooth width was 0.81 mm. It could be concluded that certain facial measurements recommended as reliable aesthetic factors for selection of suitable tooth moulds for anterior teeth restoration.